La Víctima de Trata Sexual y su Des-protección en la Ley Integral contra la Violencia de Género 1/2004 = The Sexual Trafficking Victims and Des-protection in the Law Against Gender Violence 1/2004 - Orbegozo, Izaskun (Oñati Socio-Legal Series, 2015)
In this article I make a reflection about the art. 1 L0 1/2004 of 28 December of integral Protection Measures against Gender Violence (law 1/2004) and its relations with sexual trafficking victims, who are absent in these regulation, and as a result any kind of protection.Taking into an account, the most important international instruments aiming at the elimination of violence against women, I am going to focus on sexual trafficking victims and gender violence from the point of view of criminology and victimology, and finally, on the meaning of violence gender from different perspectives, making an special mention to the concept regulated in the article 1 of the integral 1/2004.